(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Corporate social responsibility, or CSR, is a management concept that combines stakeholder and business partner interests with environmental and social issues. The 2013 Companies Act, Section 135, regulates the CSR sector in India. India has established a framework for choosing suitable corporate social responsibility (CSR) activities and made CSR a legal mandate for the first time. "Impact Assessment Studies" are used to assess how CSR programs affect target recipients and their surroundings, both directly and indirectly. This research suggests a legislative framework for the effective integration of CSR with corporation law. In this, we examine the changing corporate social responsibility (CSR) landscape in India, highlighting noteworthy traits of the emerging frameworks. It begins an outline of the new Companies Act of 2013, and corporate governance reform to comprehend backgrounds of CSR regime in India.